2021
DOI: 10.1007/s10661-021-09011-3
|View full text |Cite
|
Sign up to set email alerts
|

Meteorological patterns and the evolution of West Nile virus in an environmentally stressed Mediterranean area

Abstract: precipitation during 2018 was extremely high, nearly 500% above the average. These conditions contributed to the increase of soil moisture index anomaly and fAPAR, creating an ideal microenvironment (wet soils and green pastures) for mosquito breeding. This phenomenon was directly associated with a drastic outbreak of West Nile virus cases in the area, compared with earlier years. Our results indicate how unusually high values of summer precipitation may have contributed (both through direct and indirect ecolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Landscape, especially existence of irrigated croplands and highly fragmented forests [ 28 ] and elevation [ 30 ] are additional risk factors for WNV outbreaks. A recent study from Greece has reported the association of high levels of precipitation during summer with the rapid dispersion of WVN in West Attica [ 31 ]. Moreover, the density of infected mosquitoes has been positively associated with the number of confirmed cases in humans [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Landscape, especially existence of irrigated croplands and highly fragmented forests [ 28 ] and elevation [ 30 ] are additional risk factors for WNV outbreaks. A recent study from Greece has reported the association of high levels of precipitation during summer with the rapid dispersion of WVN in West Attica [ 31 ]. Moreover, the density of infected mosquitoes has been positively associated with the number of confirmed cases in humans [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, our findings evidence a prolonged period of virus circulation in the Peloponnese region, probably due to a seasonal change in the ecology of the virus which could be attributed to a variety of factors. It has been well documented that specific environmental parameters, such as increased ambient temperatures during summer, high precipitation in late winter/early spring or during summer and summer drought, as well as the presence of competent mosquito vectors have been associated with an increase in the virus' circulation [50][51][52][53]. A possible overwintering of the virus in the population of wild birds could be assumed, as longterm persistence of WNV in infected animals may result in the infection of birds by prey ingestion even months after the end of the mosquito season, providing a mechanism of overwintering [54,55].…”
Section: Discussionmentioning
confidence: 99%
“…It is absolutely clear and understandable that every meteorological or other phenomenon is not a natural disaster (e.g., an earthquake that occurs at sea, far from populated areas). An example from Greece is the absence of registrations regarding biological disasters, despite the fact that at least in the last decades there have been epidemics of influenza (H1N1), West Nile Virus [9], the ongoing COVID-19 pandemic, etc. But the more complete the database, the better the results of its investigation.…”
Section: Discussionmentioning
confidence: 99%